2007
DOI: 10.1090/s0025-5718-07-02056-x
|View full text |Cite
|
Sign up to set email alerts
|

A local Lagrange interpolation method based on $C^{1}$ cubic splines on Freudenthal partitions

Abstract: Abstract. A trivariate Lagrange interpolation method based on C 1 cubic splines is described. The splines are defined over a special refinement of the Freudenthal partition of a cube partition. The interpolating splines are uniquely determined by data values, but no derivatives are needed. The interpolation method is local and stable, provides optimal order approximation, and has linear complexity. §1. Introductionbe a set of points in R 3 . In this paper we are interested in the following problem. Problem 1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…We note that the algorithm is different from the general method in [4] and from the algorithm in [3] for Freudenthal partitions. In [4], the computation of the interpolating spline is based on chains of tetrahedra with common vertices and common edges, while in [3], a black and white coloring of the tetrahedra is used.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…We note that the algorithm is different from the general method in [4] and from the algorithm in [3] for Freudenthal partitions. In [4], the computation of the interpolating spline is based on chains of tetrahedra with common vertices and common edges, while in [3], a black and white coloring of the tetrahedra is used.…”
Section: Introductionmentioning
confidence: 92%
“…On the other hand, only a few results are known for this problem in the trivariate case (see [3,4,12,10]). Up to now, no Lagrange interpolation algorithms using trivariate cubic C 1 splines have been implemented.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Davydov et al showed the characterization of the interpolation set on arbitrary triangulations in [3] by investigating the zero set of bivariate linear spline. Other scholars, e.g., Chui, He, Hecklin, Nürnberger, Schumaker and Wang, did much research on this topic [1,2,4,7,10]. Nürnberger and Zeilfelder gave a summary of interpolation methods on bivariate spline spaces in [8].…”
Section: Introductionmentioning
confidence: 99%
“…Local Lagrange interpolation methods with optimal approximation order were developed recently in [14,28,18,19,15] for the spaces S 1 q ( ), q 3, and S r q ( ) for r 2 and certain q, where about half of the triangles of are split into three subtriangles. The resulting triangulation has twice as much triangles as .…”
Section: Introductionmentioning
confidence: 99%